PENERAPAN PAJAK DALAM MENINGKATKAN PENERIMAAN PAJAK PENGHASILAN FINAL SEKTOR UMKM DI KOTA KENDARI - Tandilino, Albertus (Pascasarjana Universitas Halu Oleo, 2016)
The aim of this study was to determine the effect of tax penalties services, appeal, and knowledge on revenue of final income and to determine the application of final income tax to the businesspersons in UMKM sector in Kendari city. Primary data were obtained using a questionnaire administered to 100 respondents, who were taxpayers of UMKM sector who came to KPP Kendari within the period of December 2015 until February 2016, whereas secondary data were the number of taxpayers of UMKM sector and the revenue of tax from UMKM sector in Kendari city. Using descriptive analysis, the results showed that the variable tax penalty has the greatest influence on the acceptance of the final income tax to the businesspersons in UMKM sector compared with 3 other variables. This is because the taxpayer will be penalized fear associated non-fulfillment of tax obligations. While the variable tax knowledge has the most influence is small compared three other variables. This is due to taxpayers not know the basis for determining the taxation and also do not understand that by carrying out the payment of taxes is a devotion to country. If the variable tax penalties, tax services, appeals and tax knowledge combined, would have the effect of 76.54% against the final income tax to the businesspersons in UMKM sector in Kendari city. Keywords: Tax Penalties, Tax Services, UMKM Sector